Clube de ciências e o desenvolvimento de competências científicas investigativas - Gomes, Andréia Vaz (2024)
The competency-based teaching announced by the National Common Curricular Base (BNCC) and present in the New High School has had repercussions in changes in teaching methodologies, bringing challenges and potential to educators, especially in the area of ​​Natural Sciences. In view of this, this paper addresses the importance of including, in extracurricular learning spaces, such as Science clubs, activities that encourage the development of Scientific Investigative Competencies - ICC, as a way of providing students with citizenship education. These aspects lead to the central question of the study, expressed as follows: How can the activities carried out in a Science club stimulate the development of scientific investigative competencies in participants? The objective is to develop, implement and evaluate a set of activities aimed at promoting scientific investigative competencies in high school students, through a Science club, using the Learning Station Rotation methodology. To this end, theoretical support is sought in discussions involving Science teaching, in the investigative approach and in competency-based teaching, announcing a set of seven CCI that became the focus of the actions proposed in the Science club and of the investigation of this thesis. These references supported a proposal aimed at enabling students participating in the Science club to become protagonists in the teaching-learning process, with a view to acting in society in a more autonomous, critical and conscious way. Based on the set of listed competencies and taking as a reference the Learning Station Rotation methodology, a material was prepared in the form of a support text - an educational product - to be used in Science clubs. In its preparation, the experience of the Decolar Science Club, previous studies on the subject, the pilot study carried out and the theoretical references selected for the study were considered. Based on the preparation of the educational product and with the theme of Women in Science, it was implemented in six activities developed in ten meetings, involving 16 club members from high school in a school located in the interior of Mato Grosso. To complement the activity, the study monitors the club members as they prepare their activities to be presented at a Science Fair. The research developed is based on the perspective of a qualitative and descriptive study, using four instruments for data production: observation forms filled out by external observers positioned in the work groups; semi-structured interviews with the study participants; a logbook filled out by the researcher who was responsible for implementing the activities and coordinator of the Science Club; and materials produced by the students during the activities. As a result, the study indicated the viability of the proposal in terms of promoting CCI, providing opportunities for the development of these skills, while also providing opportunities for reflections and discussions related to important topics such as women in science. This thesis is accompanied by the educational product, the central object of this study and which is available on the program's page, on the program's specific website for educational products and on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/746030).